Comportamiento de las plántulas de rosas (Rosa sp.). Injertadas en las diferentes fases de la luna: Pedro Moncayo - Ecuador 2014 - Vinueza Vinueza, Marco Vinicio (2015)
This research was developed in the Rancho San Jorge farm, located in Santa Clara neighborhood, Tupigachi parish, Canton Pedro Moncayo. It was evaluate the behavior of the rose baby plants (Rosa sp.) grafted at different phases of the moon. It was used as rootstocks, the rose known as Natal Briar and the commercial variety Cherry-O! ® was grafted . Four were the treatments evaluated: T1 (grafts in First Quarter), T2 (grafts in Full Moon), T3 (grafts in Third Quarter) and T4 (grafts in new moon). The experimental design was a DCA (completely randomized design) forty plants were determined as experimental unit and three repetitions for each moon phase were established. The variables evaluated were: percentage of seizure, days to harvest, stem length, stem diameter, length button, button diameter and exportable stems. An economic analysis to treatment was also performed. Grafts in First Quarter (T1) and full moon (T2) were the best treatments for vegetative appearance of the plant, grafts in new moon (T4) and Third Quarter (T3) had a lower growth cycle evaluated through the variable days to harvest.